Manejo de nematoides por plantas antagonistas, em solos do noroeste do Paraná, cultivados com cana-de-açúcar e olerícolas - Santana, Simone de Melo (2011)
In different pathosystems, crop rotation with antagonistic plants should be regarded as one of the main alternatives in phytonematode management given that, as well as reducing these populations, these plants can be used as green manure, mulch, for nitrogen fixing, etc. Some species have proved to be efficient in controlling the population of these parasites, such as sunn plants and velvet beans. However, there are few studies focusing on the effects of these plants in different soils and climates. Thus, the aim of this study was to evaluate the effect of crop rotations of sugarcane and lettuce with antagonistic plants (Cajanus cajan, Stizolobium aterrimum and Crotalaria spectabilis) on the phytonematode population (Pratylenchus zeae, Meloidogyne incognita and Helicotylenchus spp.) in different soils and the productivity parameters of this culture. Results from the experiment with sugarcane showed no interaction between the factors: antagonistic plants, soils and cultivation periods of the antagonistic plants. Crotalaria spectabilis and C. cajan reduced the P. Zeae population, regardless of soil type and cultivation period. Stizolobium aterrimum, despite reducing the nematode population when compared with the control, showed a reproduction factor greater than one in the two cultivation periods, in the clay soil, and after 110 days in sandy soil. The sugarcane cultivated after the antagonists in the sandy soils showed higher high plant averages than the control. Helicotylenchus spp. was also found in the samples but the data obtained during the experiment was inconsistent. In the experiment with lettuce were found statistical differences in the M. incognita populations present in the root systems and in the final population (soil + root), after the cultivation of the antagonistic plants, in comparison with the control, demonstrating the antagonistic effect of these plants on the nematode population. The number of galls on the lettuce cultivated after the antagonists was also reduced when compared to the control. The antagonists which showed the highest populations of Helicotylenchus spp. in the root systems and in the soil were the velvet bean and the pigeon pea. The velvet bean promoted an increase in the dry matter in the above-ground part of the lettuces cultivated after the antagonists.